On the scattered field generated by a ball inhomogeneity of constant index in dimension three - Capdeboscq, Y; Leadbetter, G; Parker, A (American Mathematical Society, 2012)
We consider the solution of a scalar Helmholtz equation where the potential (or index) takes two positive values, one inside a ball of radius $\eps$ and another one outside. In this short paper, we report that the results recently obtained in the two dimensional case in [1] can be easily extended to three dimensions. In particular, we provide sharp estimates of the size of the scattered field caused by this ball inhomogeneity, for any frequencies and any contrast. We also provide a broadband estimate, that is, a uniform bound for the scattered field for any contrast, and any frequencies outside of a set which tends to zero with $\eps$.